Kesalahan Penggunaan Bahasa Baku di Kalangan Siswa Teknik Elektro - Hidayat, Garneta Edlyn Putri; Nadhiroh, Ghaida Asmi; Aryoto, Ghazy Fadhilah; Rasyda, Irgi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The use of standard language in academic contexts is an essential skill, especially for Electrical Engineering students who will later engage in professional communication. However, many students struggle to apply proper Indonesian in practice. This study aims to identify the extent of Electrical Engineering students’ ability to understand and use standard Indonesian, as well as their views on the use of AI technology to support this skill. Method: The study applied a quantitative descriptive method by distributing questionnaires to 30 students from several vocational schools (SMK) in Bandung. The findings show that most students have difficulty identifying standard word and sentence forms. Nevertheless, some acknowledged the usefulness of AI in helping them construct correct sentences, although concerns about dependency that may hinder independent language use were also noted. Conclusion: A more integrative learning approach is needed, combining theory, practice, and wise use of technology, so students can use standard Indonesian proficiently and independently.